Analisis Air Tanah Menggunakan Metode Geolistrik ResistivitasKonfigurasi Schlumberger di Desa Buntu Sarong Kecamatan Masalle Kabupaten Enrekang - Munafri, Yusuf; Kusmiran, Amirin; Rahmaniah, Rahmaniah; L, Muh. Said; Rizal, Andi Syam (Journal of Health, Education, Economics, Science, and Technology, 2025)
A study has been conducted to determine the distribution of groundwater potential below the surface using the Schlumberger configuration resistivity geoelectrical method in Buntu Sarong Village, Masalle District, Enrekang Regency. The way the Schlumberger configuration works is to adjust the distance between the electrodes, where the distance between the constant voltage electrodes and the distance between the current electrodes change sequentially. This study was carried out in stages at three points. At sounding point 1, the groundwater potential is in the third layer with a resistivity value of 11.2 Ωm. This layer indicates the possibility of clay that has the potential to act as a water retainer or has a good water storage capacity. Meanwhile, at sounding point 2, the groundwater potential is in the third layer (14.4 Ωm) which indicates the presence of clay or fresh groundwater and at sounding point 3, there is a possibility of water potential in the second layer (2.28 Ωm) which indicates the presence of clay or fine sediment that is very saturated with water.